Industry Mindsets: Exploring the Cultures of Two Macro-Organizational Settings - Phillips, Margaret E. (Organization Science, 1994)
Cultures are dynamic, shared mindsets that, in organizational settings, are usually believed to be nationally or organizationally based. In this paper, the existence of industry cultures is explored. Previous studies of industry-based cognitive constructs have narrowly focused on top managers' mental models for strategic decision making. Here, broad-based assumption sets comprising the cultural knowledge widely shared among organizational participants within two industries (fine arts museums and California wineries) are surfaced and compared. A cognitive definition of culture and a modified ethnographic methodology frame the inquiry. The research process balances the requirements of the inductive method with the logistics of doing research in settings as broad in scope as “industry” and into issues as amorphous as “culture in modern organizations.” This process involves the selection and in-depth interviewing of 96 informants in 12 organizations, representing a cross-section of members of these two industries. The distinct assumption sets that surface for each industry demonstrate, among other things, substantial differences in conceptualizations of membership, competition, the origins of “truth,” the purpose of work, and the nature of work relationships. The findings suggest that the current narrow focus in research on industry-based cognitive constructs can be productively broadened to include a fuller range of cultural elements and a wider set of industry participants. The surfacing of distinct industry mindsets reinforces the emerging belief that a multiplicity of dynamic, shared mindsets exist within an organization's environment. A new cognitive lens—that of industry—is offered, through which scholars and managers alike can view behavior in organizational settings.